Proteomic analysis of oat (Avena sativa L.) under drought stress using tandem mass tag labeling - Caijin Chen; Mingfang Bao; Yanxia Zeng; Xuemin Wang; Wenhui Liu (PLoS ONE, 2025)
Drought is a major abiotic stress that limits oat growth. This study investigated the phenotypic, physiological, and proteomic differences between drought-resistant (Grain King [G]) and drought-susceptible (XiYue [X]) oat varieties under drought stress (soil water content of 15% ± 5% of field water-holding capacity) and normal conditions (soil water content of 75% ± 5% of field water-holding capacity). Phenotypic analysis showed that plant height, aboveground biomass, and underground biomass decreased under drought stress in both varieties, with variety X exhibiting a greater reduction. Physiological analysis revealed increased malondialdehyde content, soluble sugar (SS) content, and superoxide dismutase (SOD) and peroxidase (POD) activities in both varieties under drought stress, though variety X showed smaller increases. Proteomic analysis identified 151 differentially accumulated proteins (DAPs) in variety G and 792 in variety X. Further analyses showed that the DAPs in variety G, which were highly correlated with POD and SOD activities and SS content, were primarily involved in energy metabolism, protein translation, RNA processing, amino acid metabolism, and protein folding. Conversely, in variety X, the DAPs were mainly associated with RNA processing, protein stabilization, plant photosynthesis, intracellular signal transduction, and protein folding. Further analysis suggested that variety G significantly upregulated proteases related to photosynthesis, catalysts involved in citrulline synthesis, temperature-induced lipid transport proteins, fibrillin proteins linked to stress tolerance signal transduction and response, and shearing factors involved in mRNA shearing—proteins that were not significantly upregulated in variety X. These proteins may play essential roles in protecting oats from drought stress. Overall, this research elucidates the drought resistance mechanisms of different oat varieties at the protein level.